Effect of certolizumab pegol over 96 weeks in patients with psoriatic arthritis with and without prior antitumour necrosis factor exposure. Issue 1 (25th June 2015) - Mease, P; Deodhar, A; Fleischmann, R; Wollenhaupt, J; Gladman, D; Leszczyński, P; Vitek, P; Turkiewicz, A; Khraishi, M; FitzGerald, O; Landewé, R; de Longueville, M; et al.
Abstract : Objective: Previous reports of RAPID-PsA (NCT01087788 ) demonstrated efficacy and safety of certolizumab pegol (CZP) over 24 weeks in patients with psoriatic arthritis (PsA), including patients with prior antitumour necrosis factor (TNF) therapy. We report efficacy and safety data from a 96-week data cut of RAPID-PsA. Methods: RAPID-PsA was placebo-controlled to week 24, dose-blind to week 48 and open-label to week 216. We present efficacy data including American College of Rheumatology (ACR)/Psoriasis Area and Severity Index (PASI) responses, HAQ-DI, pain, minimal disease activity (MDA), modified total Sharp score (mTSS) and ACR responses in patients with/without prior anti-TNF exposure, in addition to safety data. Results: Of 409 patients randomised, 273 received CZP from week 0. 54 (19.8%) CZP patients had prior anti-TNF exposure. Of patients randomised to CZP, 91% completed week 24, 87% week 48 and 80% week 96. ACR responses were maintained to week 96: 60% of patients achieved ACR20 at week 24, and 64% at week 96. Improvements were observed with both CZP dose regimens. ACR20 responses were similar in patients with (week 24: 59%; week 96: 63%) and without (week 24: 60%; week 96: 64%) prior anti-TNF exposure. Placebo patients switching to CZP displayed rapid clinical improvements, maintained to week 96. In patients with ≥3% baseline skin involvement (60.8% week 0 CZP patients), PASI responses were maintained to week 96. No progression of structural damage was observed over the 96-week period. In the Safety Set (n=393), adverse events occurred in 345 patients (87.8%) and serious adverse events in 67 (17.0%), including 6 fatal events. Conclusions: CZP efficacy was maintained to week 96 with both dose regimens and in patients with/without prior anti-TNF exposure. The safety profile was in line with that previously reported from RAPID-PsA, with no new safety signals observed with increased exposure. Trial registration number: NCT01087788.